Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar IPS Siswa Kelas IV SD Negeri 097325 Bandar Siantar - Elprida Kristina Silalahi; Jumaria Sirait (Departement of Mathematics Education, 2023)
This study aims to determine whether the Problem Based Learning (PBL) Learning Model Affects the Learning Outcomes of Class IV Students in Subtheme 3 Learning